2013
DOI: 10.5455/cap.20130504
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in Eating Disorders

Abstract: ÖZETYeme bozukluklarında özkıyıma bağlı ölüm oranları oldukça yüksektir. Yeme bozukluklarında özkıyıma bağlı kaba ölüm hızı %0 ile %5.3 arasında değiş-mektedir. Yeme bozukluklarında özkıyım davranışı ile ilişkili etmenler, yeme bozukluğunun alt tipi, ek tanıların varlığı, ilaç metabolizmasının hızlı olması, belli kişilik özellikleri, çocuklukta istismar öyküsü ve belli aile tutumlarıdır. Bu etmenler dışında depresif bozukluklar, alkol-madde kötüye kullanımı ve kişilik bozuklukları gibi diğer ruhsal bozukluklar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In a previously published review, the death rate due to suicide in eating disorders was reported as 0%-5.3% (Öncü and Sakarya 2013). Many studies conducted so far consistently show that the risk of suicide is higher in eating disorder patients than in the normal population (Ahn et al 2019, Rania et al 2021, Udo and Grilo 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In a previously published review, the death rate due to suicide in eating disorders was reported as 0%-5.3% (Öncü and Sakarya 2013). Many studies conducted so far consistently show that the risk of suicide is higher in eating disorder patients than in the normal population (Ahn et al 2019, Rania et al 2021, Udo and Grilo 2022.…”
Section: Introductionmentioning
confidence: 99%